Features of morphology of the lower border of the maxillary sinus at various kinds of occlusion (Эндодонтия Today)
The study of location of maxillary sinus’ lower border is extremely important for various oral health providers, especially for general dentists, surgery and implantology specialists and orthodontists. The location of lower border of maxillary sinus affects dental occlusion during further rehabilitation. In order to analyse data of head telerentgenogramms made in lateral projection, form and location of lower border of maxillary sinus towards its base line (ANS-PNS) and root tip position of premolars and molars for various types of dental occlusion, we have studied 99 lateral telerentgenogramms of the scull. These TRGs were made in patients aged 20 to 45. There were 48 patients with physiological occlusion of dentition, 36 patients with distal occlusion, and 15 patients with mesial occlusion of dentition. We have identified 4 principal shapes of the lower boundary of maxillary sinus and 3 types of its vertical distance from the basis of maxilla (line ANS-PNS) in the areas corresponding to location of molar’s root tips above the lower boundary of sinus for various dental occlusions. During the study we have compared the frequency of location of molars’ root tips above the lower border of maxillary sinus for various dental occlusions. We have discovered that low position of lower border of maxillary sinus (especially in case of funnel or undulating shape of sinus) must be analysed during the process of indication selecting for distal or mesial, tipping or bodily orthodontic movements of lateral teeth.